Notes on a rapid assessment of myxomycetes for Kabylie, Algeria - Rojas Alvarado, Carlos Alonso (2010)
Studies of myxomycetes in some regions of the w orld are limited. orthern Africa is one prominent example. For this reason, a rapid assessment of myxomycete diversity in four study areas w ithin the Kabylie region of Algeria as carried out in July 2008. Fourteen different species w ere identified from specimens obtained in moist chamber cultures prepared w ith samples of dead plant material. Six of the species are taxa not previously reported for Algeria. Our preliminary data suggest that myxomycete assemblages in the region may show the influence of topographic and microclimatic factors.